The validation of the Dutch SF-Qualiveen, a questionnaire on urinary-specific quality of life, in spinal cord injury patients - Reuvers, Sarah H. M. (BMC Urol, 2017)
BACKGROUND: Optimizing the patients’ quality of life is one of the main goals in the urological management of spinal cord injury (SCI) patients. In this study we validated the Dutch SF-Qualiveen, a short questionnaire that measures the urinary-specific quality of life, in SCI patients. No such measure is yet available for this patient group. METHODS: In 2015–2016 SCI patients with urinary symptomatology who visited the outpatient clinics of Urology at the Erasmus Medical Centre and Rehabilitation at Rijndam Revalidation completed the SF-Qualiveen and UDI-6 during the visit and 1–2 weeks later. The UDI-6, a urinary tract symptom inventory, served as gold standard. Controls, recruited from the Otolaryngology outpatient clinic, completed the questionnaires once. Content-, construct-, and criterion validity and reliability (internal consistency and reproducibility) of the SF-Qualiveen were determined. RESULTS: Fifty seven SCI patients and 50 controls were included. 12 SCI patients asserted that the SF-Qualiveen covered their bladder problems (good content validity). Patients’ SF-Qualiveen scores being positively associated with severity of urinary symptoms and patients’ scores being higher than those of controls indicated good construct validity. The positive association that was found between SF-Qualiveen and UDI-6 in patients (r = 0.66–0.67, P < 0.001) and controls (r = 0.63, P < 0.001) confirmed good criterion validity. Internal consistency (Cronbach’s alpha 0.89–0.92) and reproducibility (intraclass correlation coefficient 0.94) of the SF-Qualiveen were good. CONCLUSIONS: The Dutch SF-Qualiveen is a valid and reliable tool to measure the urinary-specific quality of life in SCI patients.